PENCAPAIAN PERTUMBUHAN PADA BALITA DI PERDESAAN DAN PERKOTAAN INDONESIA - Sri Muljati; Basuki Budiman (Persagi, 2006)
Background: Protein Energy Malnutrition among children under five years old is one of the many nutrition problems in Indonesia. During this period, growth faltering frequently occurs resulting in failure to attain optimal potential growth in toddlers. Objective: To determine the age in which the most growth faltering happens and its related factors. Methods: A secondary data analysis of 1.964 children under five years old in SKRT 2004 was use for this study. Inclusion criteria were having complete data on weight. height/length, child characieristics and socio demographic data of parents. Growth trajectory was determinant based on weight for height and devided into below and normal growth Results: The analysis showed that 42.9% attained normal growth, and 51.5% living in rural area. Increase of growth failure occurred at the age of 7-10 month old compared to other age. Multivariate analysis showed that there was an increased risk of growth failure 1.5 times in children living in rural areas and 1.9 times in children of muttiparagravida (sixth or more). [Penel Gizi Makan 2006, 29(2): 68-77)